CHARACTERIZTIC MORPHOLOGY ON SEEDS OF FOUR COLLECTION PLANT THAT HAVE BEEN CULTIVATED IN PURWODADI BOTANICAL GARDEN - Husna, Firda Asmaul; Darmayanti, Agung Sri; Sulasmi, Eko Sri (Proceedings of the International Conference on Green Technology; Vol 6 No 1 (2015): Proceeding of International Conference on Green Technology, 2020)
Background: The seeds are main breeding on spermatophyte. Plant can retain its kind and spread into various places caused by the seeds. Purwodadi Botanical Gardens have various collection plants as a conservation action. Based on IUCN 2012, the conservation status of Parmentiera cereifera Seem, listed as endangered plant. Instia bijuga (Colbr.) Kuntze and Dillenia philippinensis Rolfe listed as vulnerable plant. Protium javanicum Burm F is a protected plant under the Agriculture Minister Decree‘s No 54/Kpts/Um/2/1972. Objectives: The purpose of this research is to know the pattern of morphological characters of the seeds. Several parameters were observed in morphology seeds characterization include size (length and width; cm), diameter or thickness (cm), weight (g), color, surface and shape. One hundred seeds have been observed every plant. Results: This research shows every seed have different characters. The colors brown, black and orange. Seeds have wringkled smooth and hairy surface and have many type of shape such as 3 dimention, plateriform, irregular, and pyriforrm. Conclusion: This character can be used to complement the seed character data that not listed by Beacker on Flora of java